Higher Education Ministry Secretary General joined UMP denizens in breaking of fast and iftar - UMP, PNC
Higher Education Ministry Secretary General, Datuk Ab Rahim Md Noor joined some 700 guests in breaking of fast and iftar at UMP Mosque in Gambang on July 28, 2012.